Oral Administration of the Pimelic Diphenylamide HDAC Inhibitor HDACi 4b Is Unsuitable for Chronic Inhibition of HDAC Activity in the CNS In Vivo - Beconi, Maria; Aziz, Omar; Matthews, Kim; Moumné, Lara; O’Connell, Catherine; Yates, Dawn; Clifton, Steven; Pett, Hannah; Vann, Julie; Crowley, Lynsey; Haughan, Alan F.; Smith, Donna L.; et al. (PLOS ONE, 2012)
Histone deacetylase (HDAC) inhibitors have received considerable attention as potential therapeutics for a variety of cancers and neurological disorders. Recent publications on a class of pimelic diphenylamide HDAC inhibitors have highlighted their promise in the treatment of the neurodegenerative diseases Friedreich’s ataxia and Huntington’s disease, based on efficacy in cell and mouse models. These studies’ authors have proposed that the unique action of these compounds compared to hydroxamic acid-based HDAC inhibitors results from their unusual slow-on/slow-off kinetics of binding, preferentially to HDAC3, resulting in a distinctive pharmacological profile and reduced toxicity. Here, we evaluate the HDAC subtype selectivity, cellular activity, absorption, distribution, metabolism and excretion (ADME) properties, as well as the central pharmacodynamic profile of one such compound, HDACi 4b, previously described to show efficacy in vivo in the R6/2 mouse model of Huntington’s disease. Based on our data reported here, we conclude that while the in vitro selectivity and binding mode are largely in agreement with previous reports, the physicochemical properties, metabolic and p-glycoprotein (Pgp) substrate liability of HDACi 4b render this compound suboptimal to investigate central Class I HDAC inhibition in vivo in mouse per oral administration. A drug administration regimen using HDACi 4b dissolved in drinking water was used in the previous proof of concept study, casting doubt on the validation of CNS HDAC3 inhibition as a target for the treatment of Huntington’s disease. We highlight physicochemical stability and metabolic issues with 4b that are likely intrinsic liabilities of the benzamide chemotype in general.